2008
DOI: 10.1111/j.1600-0536.2007.01305.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and consequences of hand eczema – an 8‐year follow‐up study of a population‐based twin cohort

Abstract: The clinical picture and consequences of hand eczema vary; however, the majority experience chronic symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 28 publications
7
81
1
2
Order By: Relevance
“…This agrees with previous reports. 18,22,23 The observation that ICD was the significantly most frequent subdiagnosis in women could be due to domestic wet work as a contributing factor to this subdiagnosis, and that this is traditionally a burden to female skin. The finding that ACD was related to more severe hand eczema as compared with ICD, when assessed by HECSI, contradicts recent findings in patients with OHE where ICD was found to be related to severe eczema.…”
Section: Discussionmentioning
confidence: 93%
“…This agrees with previous reports. 18,22,23 The observation that ICD was the significantly most frequent subdiagnosis in women could be due to domestic wet work as a contributing factor to this subdiagnosis, and that this is traditionally a burden to female skin. The finding that ACD was related to more severe hand eczema as compared with ICD, when assessed by HECSI, contradicts recent findings in patients with OHE where ICD was found to be related to severe eczema.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, an American study demonstrated that hand dermatitis caused a reduction in patients' quality of life, and limited their activity and work performance compared with people unaffected by the disease [54]. A 10-year Danish monitoring study of 274 hand dermatitis patients reported that 12.4% had a disease-related work stoppage, while 8.5% had to change their profession [55]. …”
Section: Discussionmentioning
confidence: 99%
“…[2] The frequency of contact sensitization in hand eczema patients varies from 23% in mild cases to 62% in severe cases. [3,4] The role of contact sensitization in increasing the severity of hand eczema has not been evaluated. Also, the role of specific allergens in different morphological forms of hand eczema is understudied.…”
Section: Introductionmentioning
confidence: 99%